ANALISIS PENGGUNAAN CORTEX DALAM MENINGGAKATKAN EFEKTIVITAS KINERJA PEGAWAI PADA PENGOLAHAN SUMBER DAYA MANUSIA - Suciani Sembiring; Rani Elisabeth Sinaga; Febrianto Sihombing; Elfins Okto Posmaida Damanik (Smart Education, 2026)
The development of artificial intelligence (AI)-based technology has encouraged organizations to adopt digital systems for human resource management, one of which is through a cortex-based system. This study aims to analyze the influence of cortex on the effectiveness of employee performance in managing human resources. The research method used was a qualitative case study approach. Data were collected through in-depth interviews, observation, and documentation involving 10 informants. The results show that cortex has a positive influence on the effectiveness of employee performance, particularly in improving efficiency, data accuracy, and work productivity. However, this influence is not optimal due to obstacles such as limited digital competency, lack of training, and resistance to change. Therefore, organizations need to strengthen human resource readiness and adaptive strategies to optimize the implementation of the cortex systemCortex